Comparison of Legal Systems in Democratic and Autocratic Countries: Implications for Human Rights - Junaidi Lubis; Melky Suhery Simamora; Siti Aisyah Binti Rahman; Muhammad Salim Fauzi; Muhammad baddawi kurniadi (Outline Publisher, 2024)
This study examines the comparative effectiveness of legal systems in democratic and autocratic countries in upholding and promoting human rights. Democratic systems, characterized by judicial independence, transparency, and accountability, generally provide a robust framework for protecting individual freedoms and ensuring equitable governance. In contrast, autocratic systems, marked by centralized power and limited oversight, often prioritize political stability over the protection of human rights, resulting in systemic abuses and marginalization of vulnerable groups. The research explores key dimensions such as judicial autonomy, freedom of expression, political participation, and the role of civil society, highlighting stark differences in how these systems function. The findings reveal that democracies offer stronger institutional mechanisms for addressing human rights challenges, including access to justice, legislative inclusivity, and adherence to international norms. Autocratic regimes, however, frequently exploit legal systems to maintain control, using laws as tools for oppression and surveillance. The study underscores the critical role of governance structures in shaping human rights outcomes, advocating for the strengthening of democratic institutions and global human rights standards. Future research should delve into hybrid systems and transitions between governance types to further elucidate their impact on human rights.